Expansion of a conserved architecture drives the evolution of the primate visual cortex - Emily E. Meyer; Marcelina Martynek; Sabine Kastner; Margaret S. Livingstone; Michael J. Arcaro (Proceedings of the National Academy of Sciences, 2025)
Human brain evolution is marked by a disproportionate expansion of cortical regions associated with advanced perceptual and cognitive functions. While this expansion is often attributed to the emergence of novel specialized brain areas, modifications to evolutionarily conserved cortical regions also have been linked to species-specific behaviors. Distinguishing between these two evolutionary outcomes has been limited by the ability to make direct comparisons between species. Here, we addressed this limitation by examining the expansion of the human visual cortex relative to macaques using a common functional architecture: retinotopy. Our findings revealed that human visual cortex expansion is primarily driven by increases in the surface area of a visual map architecture present in macaques rather than an increase in the number of individual areas. This expansion was not uniform, with higher-order areas, particularly in the parietal cortex, exhibiting the largest growth. Comparisons between neonate and adult humans revealed that these relative areal size differences were already established at birth. A meta-analysis of neuroimaging studies indicated that the most expanded areas are associated with advanced cognitive functions beyond visual processing. These results suggest that human perceptual and cognitive adaptations may be rooted in the expansion of evolutionarily conserved cortical architecture, with modifications even in the sensory cortex contributing to the broader cognitive functions characteristic of human behavior.